Implementation of the GELIS Program in the School Literacy Movement at Elementary School - Rahayu, Winanjar; Suyono; Radeni Sukma Indra Dewi; Slamet Arifin (JTP - Jurnal Teknologi Pendidikan, 2024)
The school literacy movement has become an important focus for improving the quality of education in Indonesia. One of the problems that contributes to the decline in students’ understanding of the learning process is the low interest in reading among students in Indonesia. This research involved 15 elementary school teachers and three main literacy figures. This research aims to analyze the implementation of the GELIS (School Literacy Movement) program in elementary schools. This research uses the CIPP approach, and this type of research is called descriptive evaluation. Data collection was mainly carried out through surveys, which included observation, interviews, and distributing questionnaires to research participants. The findings show that the implementation of the program was carried out using methods and strategies, namely preliminary studies, objectives, and division into several aspects of literacy, namely habituation, development, and learning programs. The results of the CIPP evaluation show that the context is in accordance with the objectives of character building and increasing student literacy, the input uses standard facilities and infrastructure but needs improvements in aspects of teacher resources, and the process is in line with expectations. The planning stages and sorting activities based on aspects and products had a positive impact, namely increasing literacy for both students and teachers, with an increase in the percentage of those in the category who "always" read a book for 15 minutes from 21.4% to 92%. And for teachers in the "always" category, the indicator of finding literacy teaching methods is effective from 7.14%, rising to 92%.